Primer immün yetersizliklerde COVID-19 hastalığı ya da COVID-19 aşılarının ortaya çıkardığı immün yanıtların araştırılması - Bulutoğlu, Alper (My University, 2023)
Giriş ve Amaç: Şubat 2020'de Avrupa'da ve Mart 2020'de Türkiye'de yaygınlaşan SARS-CoV-2'nin COVID-19 salgın olduğu düşünülür. Bu tarihlerden sonra, hastalık Dünya Sağlık Örgütü (WHO) tarafından küresel bir salgın olarak ilan edilir. SARS-CoV-2'nin özellikle riskli hasta gruplarında ciddi sonuçlara yol açabilmektedir. Primer immün yetmezlikli hastalar, bağışıklık sistemindeki zayıflık veya eksiklikleriyle riskli hasta gruplarına dahil olurlar. Doğuştan gelen bağışıklık kusurları, bağışıklık hücrelerinin veya medyatörlerin işlevsizliğine neden olabilir. Bu noktada, bu tip hastalarda COVID-19'a karşı artan risk ve ciddi sonuçlardan ortaya doğurur. Yöntem: Aşı sonrası hastalardan alınan serum örneklerinin, SARS-CoV-2'ye karşı özgün antikor miktarını belirlemek için ELISA testleri kullanılarak test edilir. ELISA testlerinde rekombinant antijenler kullanılarak antikorların ölçülür. Hücresel bağışıklık yanıtlarını ölçmek için rekombinant SPIKE proteini kullanarak in vitro deneyler yapılır. Bu deneylerde hastadan alınan Periferik Kan Mononükleer Hücreleri (PKMH) uyaran proteinlere nasıl tepki gösterdikleri incelenmiştir. Bu deneylerde hücre içi boyama yöntemi kullanılarak çeşitli sitokinlerin (IL-4, IL-10, IFN-gama, IL-17A, TNF) salgılanması ve belirli aktivasyon belirteçlerinin (CD137, CD154, Anti-Ki67, CD25) ifadesi ölçülmüştür. Bu çalışmada farklı primer immün yetmezliklerine sahip hastaların COVID-19'a karşı immün tepkilerini ve aşı sonrası bu tepkilerin nasıl değiştiğini analiz etmeyi amaçlanılmıştır. Bu sayede, bu hastaların COVID-19 enfeksiyonuna ve aşılarına nasıl yanıt verdikleri daha iyi anlaşılacak ve aşıların etkinliği hakkında bilgi sağlanmıştır. Bulgular: Primer İmmün Yetmezlik (PİY) alt grupların farklı alt gruplarında, aşıya antikor yanıtı veren ve vermeyen bireyler bulunmaktaydı. Bu bireyler aşı sonrası T hücre aktivasyon ve sitokin testlerine dahil edildi. Aşı yanıtı gözlenmeyen bazı olgularda T hücre aktivasyonu ve sitokin yanıtında düzensizlikler gözlenmiştir. ICOS eksikliği, LRBA eksikliği, Herediter Anjioödem ve ataksi telenjiektazi hastalarında T hücre aktivasyonu ve sitokin yanıtlarının genek olarak kontrollere göre düşük olmakla birlikte yüksek konsantrasyonda SPIKE antijenleri ile bir miktar uyarım ve immün cevap ortaya koyabildiği görülmüştür. Sonuç: Çalışmamızda özellikle bazı Primer İmmün Yetmezlik gruplarının SARS-CoV2 özgü immün cevaplarınını yetersiz ve sitokin yanıtlarının düzensiz olabileceği gösterilmiştir. Belirlenen alt grupların ilerideki pandemilerde ve pandemi dışı viral enfeksiyonlarda hassas bireyler olarak ele alınmalı ancak aşılama ile mümkün olduğunca koruma sağlanması hedeflenmelidir.

Background and Aim: In Europe, the emergence of SARS-CoV-2 in February 2020, followed by its presence in Turkey in March 2020, marked the onset of what would later become known as the COVID-19 pandemic. Subsequently, the World Health Organization (WHO) declared it a global epidemic. The impact of SARS-CoV-2 is particularly severe among vulnerable patient populations, and individuals with primary immunodeficiency fall into this category due to inherent weaknesses or deficiencies in their immune systems. Defects in the innate immune system can result in impaired immune cell functionality or mediator functions. Consequently, individuals with such immune-related vulnerabilities face an elevated risk of contracting COVID-19 and experiencing severe outcomes. Method: Serum samples obtained from vaccinated patients underwent ELISA tests to quantify the specific antibodies against SARS-CoV-2. Additionally, in vitro experiments employed the recombinant SPIKE protein to assess cellular immune responses, particularly how they influence Peripheral Blood Mononuclear Cells (PBMCs) harvested from patients. During these experiments, we investigated the secretion of various cytokines (IL-4, IL-10, IFN-gamma, IL-17A, TNF) and gauge the expression of specific activation markers (CD137, CD154, Anti-Ki67, CD25) using the intracellular staining method. The overarching goal of this study was to scrutinize the immune responses exhibited by individuals with diverse primary immunodeficiencies in the context of COVID-19 and track any alterations in these responses following vaccination. This comprehensive analysis aims to enhance our understanding of how these patients react to both COVID-19 infection and vaccines. Ultimately, it will provide valuable insights into the effectiveness of vaccines in this particular patient population. Results: Our investigation revealed that a subset of individuals with Primary Immunodeficiency Disorders (PID) exhibited a deficiency in generating antibodies in response to SARS-CoV-2 vaccination. In our study, we examined the relationship between T cell immune responses, encompassing activation and cytokine production, and the capacity for antibody production. Our findings demonstrated that patient T cells displayed reduced responsiveness to the SARS-CoV-2 antigen when compared to those of healthy donors, accompanied by dysregulated cytokine production. Interestingly, we observed that a higher concentration of the SPIKE protein led to increased T cell activation and improved cytokine production in these individuals, although these levels remained below those observed in healthy individuals. Conclusion: Our research demonstrates that certain Primary Immunodeficiency Disorders (PID) are associated with impaired immune responses and irregular cytokine production when exposed to SARS-CoV-2 antigens in in vitro settings. It is crucial to recognize that individuals with these specific PID subsets may face a heightened risk of severe illness during future pandemics or encounters with other viral infections. Implementing immunization strategies could potentially bolster their immune responses, ultimately mitigating the severity of infections.
Investigation of the immune responses caused by COVID-19 disease or COVID-19 vaccines in primary immune deficiencies
Keywords: Aşı COVID-19; Aşılama; Aşılar; Child; COVID-19; COVID-19 (Disease); COVID-19 (Hastalık); Çocuk; PID; PİY; T Cell; T Hücre; Vaccination; Vaccine; Vaccines